Pengaruh Kompetensi dan Motivasi Kerja terhadap Kinerja Karyawan di PT. Inti Kebun Sejahtera - Adji Sigit Sutedjo; Anwar Prabu Mangkunegara (Universitas Negeri Surabaya, 2018)
This research aims to identify and analyze the influence of Competence and Work Motivation on Employee Performance at PT. Inti Kebun Sejahtera located in Sorong - West Papua. This study uses a quantitative approach with causality analysis, sampling techniques using Propotionate Stratified Random Sampling of 155 respondents from each of the areas of work, namely Planting Group (planting, survey), Upkeep Group (Fertilization, Spraying and Slashing) and Harvesting Group (Harvest, Fruit Loose Collection, and Prunning). The result that the values of multiple regression in this study is Y = 7.280 + 0.437 X1 + 0.530 X2 + e. the results of this study indicate that partial and simultaneous, variable Competence and Work Motivation has positive influence and significant impact on Employee Performance of Contractor Workers in PT. Inti Kebun Sejahtera. It is evident from the results of the partial test (t test) Competency variable is 3.111 with significant value of 0.002, then the value of the variable Work Motivation t test was 4.569 with significant value of 0.000). Then the results of the simultaneous test (F test) variable Competence and Work Motivation is 156.911 with a significant value of 0.000.